POLA KOMUNIKASI KELUARGA DALAM PENERAPAN FUNGSI KELUARGA PADA ANAK PELAKU TINDAK ABORSI DI JAKARTA PUSAT - Yulie Echa Savitri; Maulana Rezi Ramadhana (Ilmu Komunikasi, FISIP Universitas Pasundan, 2020)
ABSTRACT Abortion among adolescents is caused by low family control and lack of good communication so that good communication and family functions are needed as a vehicle to educate family members for the achievement of a prosperous family, because the lower functioning of a family, juvenile delinquency will be higher and vice versa. This study aims to determine how family communication patterns in implementing family functions in abortion perpetrators using the theory of family communication patterns from Fitzpatrick and Koerner. The research method used is qualitative with a phenomenological approach with a constructivist paradigm. The results of this study indicate that family communication patterns in the application of family functions through conversation orientation and conformity in abortion children have a dominant function applied, namely the function of religion and protection, another function which is still applied is the reproductive function. Also found differences in family communication patterns in emphasizing family functions, especially on religious functions and protection functions based on the experience of children who have abortions.